Friedrich Hayek and Michael Polanyi in Correspondence. Issue 1 (2nd January 2016) - Jacobs, Struan; Mullins, Phil
Summary: Friedrich Hayek and Michael Polanyi corresponded with each other for the best part of thirty years. They had shared interests that included science, social science, economics, epistemology, history of ideas and political philosophy. Studying their correspondence and related writings, this article shows that Hayek and Polanyi were committed Liberals but with different understandings of liberty, the forces that endanger liberty, and the policies required to rescue it.